Castrate-resistant prostate cancer: the right targets and combinations. Issue 1 (January 2008) - Karakunnel, Joyson; Dahut, William
Metastatic prostate cancer is the second leading cause of death in the USA. There are currently limited chemotherapeutic agents in the treatment of castrate-resistant prostate cancer (CRPC). Currently, docetaxel is the only approved chemotherapeutic agent that has been able to show a survival advantage. There have been several trials of other chemotherapeutics that have not been able to show a survival advantage, and this led to greater toxicity. As different molecular targets are discovered, there are opportunities for targeted therapies for metastatic prostate cancer. In addition, exploration of targeted combination therapies has led to further advances. This article reviews some of the recent targets and trials being used in combination therapy for CRPC.